2022
DOI: 10.1155/2022/3034150
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of RACGAP1 Promotes Progressions of Hepatocellular Carcinoma Regulated by GABPA via PI3K/AKT Pathway

Abstract: Hepatocellular carcinoma (HCC) is one of the dominating tumors causing death due to lack of timely discovery and valid treatment. Abnormal increase of Rac GTPase activating protein 1 (RACGAP1) has been verified to be an oncogene in plenty tumors. The profound mechanism of RACGAP1 was rarely reported in HCC. In this study, we explored the function and mechanism of RACGAP1 in HCC through multiple analysis and experiments. RACGAP1 expression was up-regulated in HCC samples and the high expression of RACGAP1 was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As ECT2 showed important roles in affecting the clinical outcome, tumor stage, grade, and immune cell infiltration, we investigated the molecular interactions of ECT2, where two proteins, namely RACGAP1 and KIF23, were common ones in the two lists of “ECT2-interacting” and “ECT2-correlated” proteins. It was not a surprise that both of these proteins correlated with the progression of several types of human cancers [ 94 , 95 , 96 , 97 ]. Consequently, this interaction pathway could be a potential target for novel antitumor medications.…”
Section: Discussionmentioning
confidence: 99%
“…As ECT2 showed important roles in affecting the clinical outcome, tumor stage, grade, and immune cell infiltration, we investigated the molecular interactions of ECT2, where two proteins, namely RACGAP1 and KIF23, were common ones in the two lists of “ECT2-interacting” and “ECT2-correlated” proteins. It was not a surprise that both of these proteins correlated with the progression of several types of human cancers [ 94 , 95 , 96 , 97 ]. Consequently, this interaction pathway could be a potential target for novel antitumor medications.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, high nuclear RACGAP1 expression is associated with poor survival in patients with colorectal cancer ( 51 ). In HCC, RACGAP1 overexpression promotes disease progression and has been reported to be significantly associated with worse overall survival ( 16 , 17 ). In the present study, knockdown of RACGAP1 significantly suppressed cell proliferation and induced apoptosis, whilst overexpression of RACGAP1 significantly promoted cell proliferation and suppressed apoptosis in Huh-7 and Hep3B cells under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of RACGAP1 has been implicated in the pathogenesis and progression of numerous malignant tumors ( 14 , 15 ). For example, recent studies have reported that upregulation of RACGAP1 can be an indicator of a worse overall survival rate in patients with HCC ( 16 ). The activation of RACGAP1 and demethylation of its promoter region, specifically at the H3K4me2 site, have been reported to promote early recurrence, metastasis and microvascular invasion in HCC ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…To further confirm and evaluate potential therapeutic values from the novel identified up-regulated DEGs with the impacts of decreased survival in the current study, we chose to validate genes that were the top ten up-regulated DEGs with decreased survival and not shown to be associated with tumorigenesis. Among them, studies have proved that CCNB1, RACGAP1 and NUSAP1 promote the progression of multiple cancers (Aljohani et al 2022;Gu et al 2022;Guo et al 2020), and NCAPG and CCNB2 have been found to be associated with a poor prognosis of ES (Kakar et al 2022;Zhao et al 2022), while ASPM, CENPF, CKS2, and DTL have not been studied in ES to the best of our knowledge. Interestingly, these four genes were also found in the GO analysis and GSEA results (Fig.…”
Section: In Vitro Verification Of Four Up-regulated Degs With Decreas...mentioning
confidence: 97%